VALES – IV. Exploring the transition of star formation efficiencies between normal and starburst galaxies using APEX/SEPIA Band-5 and ALMA at low redshift. Issue 1 (8th December 2017) - Cheng, C; Ibar, E; Hughes, T M; Villanueva, V; Leiton, R; Orellana, G; Muñoz Arancibia, A; Lu, N; Xu, C K; Willmer, C N A; Huang, J; Cao, T; et al.
Abstract: In this work, we present new the Swedish-ESO PI receiver for the Atacama Pathfinder Experiment APEX/SEPIA Band-5 observations targeting the CO ( J = 2–1) emission line of 24 Herschel-detected galaxies at z = 0.1–0.2. Combining this sample with our recent new Valparaíso ALMA Line Emission Survey (VALES), we investigate the star formation efficiencies [SFEs = star formation rate (SFR)/M_H_2 ] of galaxies at low redshift. We find the SFE of our sample bridges the gap between normal star-forming galaxies and Ultra-Luminous Infrared Galaxies (ULIRGs), which are thought to be triggered by different star formation modes. Considering the SFE΄ as the SFR and the L^′ _CO ratio, our data show a continuous and smooth increment as a function of infrared luminosity (or star formation rate) with a scatter about 0.5 dex, instead of a steep jump with a bimodal behaviour. This result is due to the use of a sample with a much larger range of sSFR/sSFRms using LIRGs, with luminosities covering the range between normal and ULIRGs. We conclude that the main parameters controlling the scatter of the SFE in star-forming galaxies are the systematic uncertainty of the αCO conversion factor, the gas fraction, and physical size.